Production of ferulic acid from oryzanol degradation during the fermentation of black rice bran by ferulic acid esterase producing Aspergillus oryzae HP - Sasithorn Sirilun (2018)
© 2015, Journal of Pure and Applied Microbiology. All rights reserved. Rice bran (RB) is the known source for phenolic acids, anthocyanins, flavonoids, steroidal compounds, polymeric carbohydrates, proteins and essential nutrients like vitamin B, E, γ-oryzanol, ferulic acid and inositol. Ferulic acid (FA), an ingredient for therapeutics, can be produced from oryzanol by ferulic acid esterases (FAE). The present study deals with the screening and production of FA from RB by Aspergillus oryzae. About 21 strains were screened through plate assays and spectrophotometric analysis. A. oryzae HP 36 has been identified as potent FAE producer (3.20 ± 0.10 mm) among the tested strains and optimum incubation up to 72 h yielded maximum of ~ 2.16 ± 0.05 µmol/ h of FAE. RB fermentation by A. oryzae HP 36 resulted in the production of 311.18 ± 15.6 µg of FA/ 5 g of RB. High-performance liquid chromatography (HPLC) analysis of FA and oryzanol content in fermented samples also supports the formation of FA from oryzanol during fermentation. This primary study, represent the efficiency of ferulic acid esterase of A. oryzae in naive condition and use of RB as substrate for FA production. Further, characterization of FAE and standardization of fermentation conditions are under progress to achieve improved FA production.